Safety of COVID-19 vaccine in patients with myasthenia gravis: a self-controlled case series study - Ruan, Zhe; Huan, Xiao; Su, Yue; Tang, Yong-Lan; Meng, Dong-Dong; Ren, Da-Lin; Li, Chun-Hong; Hao, Si-Jia; Zhao, Chong-Bo; Luo, Su-Shan; Li, Zhu-Yi; Chang, Ting (Frontiers in Immunology, 2023)
Background: The safety of COVID-19 vaccines has been clarified in clinical trials; however, some immunocompromised patients, such as myasthenia gravis (MG) patients, are still hesitant to receive vaccines. Whether COVID-19 vaccination increases the risk of disease worsening in these patients remains unknown. This study aims to evaluate the risk of disease exacerbation in COVID-19-vaccinated MG patients. Methods: The data in this study were collected from the MG database at Tangdu Hospital, the Fourth Military Medical University, and the Tertiary Referral Diagnostic Center at Huashan Hospital, Fudan University, from April 1, 2022, to October 31, 2022. A self-controlled case series method was applied, and the incidence rate ratios were calculated in the prespecified risk period using conditional Poisson regression. Results: Inactivated COVID-19 vaccines did not increase the risk of disease exacerbation in MG patients with stable disease status. A few patients experienced transient disease worsening, but the symptoms were mild. It is noted that more attention should be paid to thymoma-related MG, especially within one week after COVID-19 vaccination. Conclusion: COVID-19 vaccination has no long-term impact on MG relapse.